My name was Eden : a novel - Barker-White, Eleanor (William Morrow, 2024)
"In this unsettling psychological debut, a mother's experience with Vanishing Twin Syndrome results in disturbing changes in her teenage daughter, perfect for fans of The Push and The Undoing"--